2020
DOI: 10.1177/2515690x20967323
|View full text |Cite
|
Sign up to set email alerts
|

Valerian Root in Treating Sleep Problems and Associated Disorders—A Systematic Review and Meta-Analysis

Abstract: Sleep problems are widely prevalent and associated with various comorbidities including anxiety. Valerian ( Valeriana officinalis L.) is a popular herbal medicine used as a sleep aid, however the outcomes of previous clinical studies are inconsistent. This study was conducted to update and re-evaluate the available data in order to understand the reason behind the inconsistent outcomes and to provide a broader view of the use of valerian for associated disorders. PubMed, ScienceDirect, and Cochrane Library wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 154 publications
1
60
0
2
Order By: Relevance
“…[308]. Valerian preparations have further been shown to encourage sleep, improve sleep quality, and reduce blood pressure [309]. Additionally, the root is known for its mild anodyne, hypnotic, carminative, and hypotensive properties [301].…”
Section: Valeriana Officinalismentioning
confidence: 99%
See 1 more Smart Citation
“…[308]. Valerian preparations have further been shown to encourage sleep, improve sleep quality, and reduce blood pressure [309]. Additionally, the root is known for its mild anodyne, hypnotic, carminative, and hypotensive properties [301].…”
Section: Valeriana Officinalismentioning
confidence: 99%
“…Additionally, the root is known for its mild anodyne, hypnotic, carminative, and hypotensive properties [301]. Sleep promotion and anxiolytic effects are the major therapeutic benefits expected from V. officinalis herb [308,309], and thus have been a major research focus, as extensively reviewed only recently [309]. Neverthless, those responsible components and underlying mechanisms remain obscure [310].…”
Section: Valeriana Officinalismentioning
confidence: 99%
“…One of the most commonly used herbal medicines for insomnia is Valeriana officinalis. In a recent study, Shinjyo and colleagues, in their systematic review with meta‐analysis, concluded that valerian root could be a safe and useful herb to treat sleep problems 99 . Notably, they also reported no severe adverse events associated with valerian intake.…”
Section: Non‐pharmacologic Therapiesmentioning
confidence: 99%
“…Recently, Shinjyo et al [ 173 ], based on a systematic review of 60 studies and meta-analyses, updated and re-evaluated the most reliable literature data to assess the effectiveness of V. officinalis in ameliorating sleep and sleep-associated disorders, yet controversial and not fully conclusive. The authors reported that the inconsistent and conflicting results of the clinical trials are maybe due to the quality and to the differences in herbal preparation in addition to the aforementioned methodological limits verified.…”
Section: Preclinical and Clinical Effectiveness In Humans And Patentsmentioning
confidence: 99%
“…The therapeutic effects on sleep were found with the use of doses of 450–1410 mg of the whole root per day for up to 8 weeks. These positive biological activities could be ensured by the standardization and characterization of the phytochemical profile of the diverse active compounds present in extracts and could be improved by the combination with different sleep-promoting herbs [ 173 ]. N. grandiflora is another species tested in a preliminary clinical study; the principle compound jatamansone obtained from the rhizomes significantly reduced aggressiveness and restlessness in hyperkinetic children [ 153 ].…”
Section: Preclinical and Clinical Effectiveness In Humans And Patentsmentioning
confidence: 99%